Association of elevated fractional exhaled nitric oxide concentration and blood eosinophil count with severe asthma exacerbations - Price, David B. (Clin Transl Allergy, 2019)
BACKGROUND: Blood eosinophil count (BEC) and fractional exhaled nitric oxide (FeNO) concentration are established biomarkers in asthma, associated particularly with the risk of exacerbations. We evaluated the relationship of BEC and FeNO as complementary and independent biomarkers of severe asthma exacerbations. METHODS: This observational study included data from the Optimum Patient Care Research Database. Asthma patients (18–80 years) with valid continuous data for 1 year before FeNO reading, ≥ 1 inhaled corticosteroid prescription, and BEC recorded ≤ 5 years before FeNO reading were separated into cohorts. Categorisation 1 was based on the American Thoracic Society criteria for elevated FeNO concentration (high: ≥ 50 ppb; non-high: < 25 ppb) and BEC (high: ≥ 0.300 × 10(9) cells/L; non-high: < 0.300 × 10(9) cells/L). Categorisation 2 (FeNO concentration, high: ≥ 35 ppb; non-high: < 35 ppb) was based on prior research. Reference groups included patients with neither biomarker raised. RESULTS: In categorisation 1, patients with either high FeNO or high BEC (n = 200) had a numerically greater exacerbation rate (unadjusted rate ratio, 1.31 [95% confidence interval: 0.97, 1.76]) compared with patients in the reference group. Combination of high FeNO and high BEC (n = 27) resulted in a significantly greater exacerbation rate (3.67 [1.49, 9.04]). Similarly, for categorisation 2, when both biomarkers were raised (n = 53), a significantly greater exacerbation rate was observed (1.72 [1.00, 2.93]). CONCLUSION: The combination of high FeNO and high BEC was associated with significantly increased severe exacerbation rates in the year preceding FeNO reading, suggesting that combining FeNO and BEC measurements in primary care may identify asthma patients at risk of exacerbations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13601-019-0282-7) contains supplementary material, which is available to authorized users.